Jewish-Christian Dialogues in Middle-Byzantine Hagiography - De Ridder, Niels ca. 20./21. Jh. (2022)
This article analyzes Jewish-Christian dialogues from four hagiographical works, the Life of Neilos of Rossano (BHG 1370), the Life of Theodore of Edessa (BHG 1744, in which is included the Passion of Michael the Sabaite) and the Life of Antony the Younger (BHG 142). These dialogues, varying strongly in length, all share formal characteristics among each other and with non-hagiographical dialogues that make them stand out from the rest of the text, making them embedded dialogues. The (fictional) confrontations between Jews and Christians in these works give an insight in the Byzantine conception of Jews as the Other to the majority Christian identity in a period in which a number of emperors ordered the forceful conversion of Jews to Christianity.
Keywords: Hagiography; Dialogues; Othering; Macedonian Dynasty; Life of Neilos of Rossano; Life of Theodore of Edessa; Passion of Michael the Sabaite; Life of Antony the Younger